Yoga’s Impact on Personal and Community Development: A Study of Karmayogi Wellness in Pokhara - Basnet, Deepa (Academia Journal of Humanities & Social Sciences, 2024)
This study explores the influence of yoga on personal and community development. The research was conducted at Karmayogi Wellness in Pokhara and aims to explore the impact of yoga through a survey involving 58 participants, utilizing quantitative methods. The community’s positive perception of yoga is evident, highlighting its holistic potential for promoting well-being and community development. The findings are presented visually through the figures depicting responses related to physical fitness, mental health, and lifestyle choices, measured on a Likert scale. Overall, the community maintains a favorable view of yoga’s influence, which is further discussed in the subsequent sections. This research provides valuable insights and ideas of yoga for individuals interested in well-being and both personal and community development.